Informal irrigation in urban West Africa: an overview - Drechsel, Pay; Graefe, Sophie; Sonou, M.; Cofie, Olufunke O. (International Water Management Institute, 2006)
This report tries to provide a state-of-the-art overview on irrigated urban agriculture in the W est African subregion based on a com prehensive literature review supported by the results of three IWMI FAO projects.